Voting Preferred Shares and Corporate Control: Impact on Minority Stockholders’ Rights - Cayanan, Arthur S (Philippine Management Review, 2023)
This paper discusses the concerns related to the issuance of voting preferred shares by selected listed Philippine companies. These concerns include the rationale behind the issuance of these voting preferred stocks, limited access to the issue to controlling stockholders, very low offer prices relative to the common shares, non-listing of these securities in the Philippine Stock Exchange (PSE), and the dilution of minority stockholders’ voting rights as a consequence of issuing these stocks.